2014
DOI: 10.13000/jfmse.2014.26.1.148
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis on the Effectiveness of Smart-Learning

Abstract: The purpose of this research was to analyze the effects of smart learning. By using meta analysis method, twenty MA and Ph.D degree papers published from 2006 to 2013 were analyzed and 104 effect sizes were calculated. Followings were the results of the research: (a) Smart learning turned out to be more statistically effective comparing to traditional education. The total mean effect size was .886 and the value of U3 was 66.53%. (b) All effect size of sub dependent variables(ie, academic achievement, learning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…In Russia, research by Konovalova et al (2018) In Korea, a study by Han, Kim, and Heo (2014) using a meta-analysis method to analyze twenty articles published in Korea from 2006 to 2013 for investigating the effectiveness of Smart Education as defined by MEST (2011) showed that (a) Smart education is statistically more effective than traditional education; (b) All effect sizes of dependent variables such as academic achievement, academic satisfaction, learning attitudes are also effective through adaptation to smart education; (c) the moderated variables such as learner characteristics, learning content, and interaction are highly effective.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Russia, research by Konovalova et al (2018) In Korea, a study by Han, Kim, and Heo (2014) using a meta-analysis method to analyze twenty articles published in Korea from 2006 to 2013 for investigating the effectiveness of Smart Education as defined by MEST (2011) showed that (a) Smart education is statistically more effective than traditional education; (b) All effect sizes of dependent variables such as academic achievement, academic satisfaction, learning attitudes are also effective through adaptation to smart education; (c) the moderated variables such as learner characteristics, learning content, and interaction are highly effective.…”
Section: Literature Reviewmentioning
confidence: 99%